2019
DOI: 10.7554/elife.48498
|View full text |Cite
|
Sign up to set email alerts
|

Repressive H3K9me2 protects lifespan against the transgenerational burden of COMPASS activity in C. elegans

Abstract: In Caenorhabditis elegans, mutations in WDR-5 and other components of the COMPASS H3K4 methyltransferase complex extend lifespan and enable its inheritance. Here, we show that wdr-5 mutant longevity is itself a transgenerational trait that corresponds with a global enrichment of the heterochromatin factor H3K9me2 over twenty generations. In addition, we find that the transgenerational aspects of wdr-5 mutant longevity require the H3K9me2 methyltransferase MET-2, and can be recapitulated by removal of the putat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…Rather, loss of H3K4me3 may indirectly affect chromatin structure, and hence transcription on the X. Consistent with such a model, inactivation of SET1/COMPASS subunits results in global changes in repressive H3K9 methylation in both yeast and worms (Robert et al, 2014;Lee et al, 2019;Greenstein et al, 2020) and alters chromatin organization [(Herbette et al, 2017) (see text footnote 1)].…”
Section: Discussionmentioning
confidence: 77%
“…Rather, loss of H3K4me3 may indirectly affect chromatin structure, and hence transcription on the X. Consistent with such a model, inactivation of SET1/COMPASS subunits results in global changes in repressive H3K9 methylation in both yeast and worms (Robert et al, 2014;Lee et al, 2019;Greenstein et al, 2020) and alters chromatin organization [(Herbette et al, 2017) (see text footnote 1)].…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, Lee et al [45] recently reported that elevated levels of H3K9me2 at specific regions are associated with longer lifespan. Comparing their H3K9me2 profiles from mixed stage worms revealed a strong statistically significant overlap between the regions that showed age-dependent gain in H3K9me3 in our glp-1 mutant data with the H3K9me2 enriched regions in the long-lived strains (S8B Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the transgenerational inheritance of repressive histone modifications occurs in C. elegans mutants lacking the COMPASS complex component, WDR-5. wdr-5 mutants transgenerationally extend lifespan due to the accumulation of H3K9me2 across generations (Greer et al, 2010;Lee et al, 2019). Histone methylation may also be transmitted across generations in vertebrates (Brykczynska et al, 2010;Hammoud et al, 2009;Wu et al, 2011;Zheng et al, 2016;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%